Writing for eternity: a survey of epigraphy in Southeast Asia - Perret, Daniel (Études thématiques, 2018)
This book provides a general survey of epigraphy in Southeast Asia. Epigraphy is an academic discipline for the scientific study of all kinds of inscriptions on durable media. Despite the fact that interest in inscriptional materials goes back more than two centuries in Southeast Asia, until now the field had never been the subject of a panorama, an introduction, or a general discussion. Thomas Stamford Raffles was the first in Southeast Asia, precisely in 1815, to emphasise the importance of inscriptions for linguistics, the study of religions and history in general. Until the middle of the second millennium CE, apart from a number of religious and literary texts, inscriptions in fact constituted unique local written sources providing detailed, accurate, and often well dated historical data for many aspects of ancient life in Southeast Asia. The concept underlining this volume is that of corpus, a set of documents brought together according to various criteria. In the field of epigraphy, these corpora are crucial tools informing multiple fields of analysis for historians. This volume gathers together eighteen contributions by renowned scholars of Southeast Asian epigraphy and history whose essays are focused on corpora of inscriptional materials written using Indian scripts and local variants, Chinese script, or Arabic script and local variants. Other corpora are discussed in the introduction to this volume, in order to try to provide the fullest possible overview.
Keywords: Aufsatzsammlung; Südostasien; Epigraphik; Inschrift